Effect of Fermentation Parameters on Extra Cellular Tannase Production by Lactobacillus plantarum MTCC 1407 - Kannan Natarajan; Aravindan Rajendran (E-Journal of Chemistry)
Lactobacillus plantarum MTCC 1407 represents a valuable source of an economically attractive stable long-life tannase with potential for application in various industries. The effect of fermentation parameters such as pH, temperature and agitation speed on the growth of biomass and production of tannase using liquid medium were determined at the end of fermentation period. The optimum values of pH, reaction temperature and agitation speed for tannase activity were 6.0, 30 °C and 125 rpm respectively. The maximum tannase activity was found to be 9.29 U/mL.